Re-imagining Redemption: Universal Salvation in the Theology of Julian of Norwich1 - Walsh, Maureen L. (Horizons, 2012)
The revelations Julian of Norwich received in 1373 provided her with unique insight that transformed her understanding of the Christian faith and prompted her to re-imagine traditional notions of sin, God's love, and salvation in new ways. Her re-interpretation of these doctrines causes great anxiety for Julian inasmuch as what she learned from her showings was at odds with church teachings, particularly her new understanding of God's plan of salvation for all humanity. I argue that Julian develops a theology of universal salvation characterized by an open understanding of who will participate in the salvation of Christ, and this openness places Julian in tenuous relationship with the church of her day. Ultimately, Julian's trust that "all will be well" allows her to push beyond the tension between her insight and church teachings, in effect challenging the official teaching of no salvation for those outside the church.